Regulation of hepatic regeneration in rats by synergistic action of insulin and glucagon. - Bucher, M L (1975)
Rats were subjected to resection of the gastrointestinal tract, pancreas, and spleen, and maintained by c-ntinuous intravenous infusion. Such animals, receiving only electrolytes and glucose, and deprived of a portal blood supply, responded to 68% hepatectomy with a significant rise in hepatic DNA synthesis, which was, however, greatly delayed and diminished compared to normal controls. The activity was restored to normal by infusion of insulin and glucagon (supplemented with glucose and amino acids), but not by either hormone alone; it was not decreased by delaying the start of hormone treatment for 6-7 hr after partial hepatectomy. Infusion of insulin and glucagon into a small series of rats with intact livers did not appreciably elevate DNA synthesis. In normal rats partial hepatectomy is followed by an abrupt fall in portal vein insulin concentration. These findings are all consistent with the suggestion that agents other than insulin and glucagon may serve to initiate hepatic regeneration, but that these two hormones acting synergistically are major regulators of the rate and perhaps also the extent of the regenerative process.